A case study of the sentence final particle “BA” ’s pragmatic functions in chinese-speaking children - Zhang, Di; Wang, Zhibo; Elliott, Robert (Southeast Asia Early Childhood Journal, 2018)
The process of the language acquisition of children is reflected in two aspects; language structure and pragmatic functions. Data from "The Longtime Tracing Oral Corpus of Typical Development Children" (one child; 2,367 sentences) are analyzed. This study examines the child’s sentence final particle (SFP) “ba”, in which we focused on the intention of this word and concluding with the core pragmatic meaning and divided the different levels of “ba”. In this way, we combined the different sentence types, the intentions of utterance, and the degrees of “undetermined intention” and researched on the pragmatic function of child’s SFP “ba” in order to obtain the pragmatic acquisition of “ba” at the specific development period (1;12-4;01). The acquisition and development of children’s language is the result of a combination of biological factors, discourse input, and cognitive ability. Finally, the enlightenment of the research conclusions on early childhood education are pointed out.